PENGARUH ENDORSMENT DAN LIVE TIKTOK TERHADAP KEPERCAYAAN PELANGGAN PADA DAVIENA SKINCARE DI KOTA PROBOLINGGO - Zakaria Zakaria; Yosi Affandi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Currently, Tiktok has become a significant digital marketing platform widely utilized by businesses as an online shopping platform. This applies to Daviena Skincare products which utilize endorsements and Live Tiktok to enhance customer trust. The main objective of this research is to determine the significant influence of Endorsements and Live Tiktok on customer trust in Daviena Skincare.This study adopts a quantitative research approach. Non-probability sampling was used with purposive sampling technique, distributing an online questionnaire to 100 followers of Daviena Skincare's Tiktok account. The results of this study demonstrate that the data used is valid and reliable higher levels of endorsements and Live Tiktok correspond to higher customer trust. Specifically, endorsements partially influence customer trust, while Live Tiktok significantly affects customer trust. Simultaneous testing indicates that both endorsements and Live Tiktok positively influence customer trust. Based on the findings of this research, it can be concluded that both endorsements and live Tiktok have a positive impact on customer trust. It is recommended that the company enhances endorsements by recruiting trending celebrities for live Tiktok sessions to prevent customer churn and build customer trust.